La délivrance des actes d’urbanisme dans la wilaya de Mila : procedures et contraintes - Chebli, Nora; layeb, Hafid (Journal of Human Sciences, 2022)
The public authorities in Algeria have introduced a range of town planning acts for the establishment, production, training and transformation of buildings, the economic and relevant management of the land and the protection of the environment. This article attempts to elucidate the following main questions: What are the urban planning acts that manage urban space? Do they meet expectations in terms of town planning? How to meet the requirements formulated with regard to the buildings intended for a given use, how are these operations carried out in the wilaya of Mila through the municipal one-stop-shops and the one-stop-shop of the wilaya?